Latent period and incubation period with associated factors of COVID-19 caused by Omicron variant - Jiang, X L; Qiu, Y; Zhang, Y P; Yang, P; Huang, B; Lin, M; Ye, Y; Gao, F; Li, D; Qin, Y; Li, Y; Li, Z J (Zhōnghuá yùfáng-yīxué zázhì, 2023)
To estimate the latent period and incubation period of Omicron variant infections and analyze associated factors. From January 1 to June 30, 2022, 467 infections and 335 symptomatic infections in five local Omicron variant outbreaks in China were selected as the study subjects. The latent period and incubation period were estimated by using log-normal distribution and gamma distribution models, and the associated factors were analyzed by using the accelerated failure time model (AFT). The median ( , ) age of 467 Omicron infections including 253 males (54.18%) was 26 (20, 39) years old. There were 132 asymptomatic infections (28.27%) and 335 (71.73%) symptomatic infections. The mean latent period of 467 Omicron infections was 2.65 (95% : 2.53-2.78) days, and 98% of infections were positive for nucleic acid test within 6.37 (95% : 5.86-6.82) days after infection. The mean incubation period of 335 symptomatic infections was 3.40 (95% : 3.25-3.57) days, and 97% of them developed clinical symptoms within 6.80 (95%